Human Footprint on Natural Systems: Missing Post-war Scenario in the Urban Context of Damascus - Laurini, Eleonora; Mousli, Kindah; Alayoubi, Sedrah (International Journal of Architectural Engineering Technology, 2023)
All regions in Syria have witnessed a decline in green spaces due to the spread of illegal logging operations and a decline in interest in agricultural wealth due to the need for construction with the growing population during the past decade. In addition to the burning and destruction of many of them due to the war actions that took place during the period of the Syrian crisis, a war that affected the urban, architectural, and human fabric of the city alike, Damascus lacks sufficient green spaces compared to the cement blocks and its external facades considering global climate change. This unjust urban expansion, accompanied by the impact of the fires caused by the war, damaged humans and environment, extending from the heart of the city to its countryside and contributing to the erosion of its Ghouta in particular, the lung and living breath of Damascus, According to what we observe today, the dominance of the cement mass in the city plan of Damascus, with the lack of balance between it and the green space of gardens, public spaces, and public places.